Analysis, Findings, and Recommendations for Needs/Problems Assessment and Clustering of UMKM Assisted by CDA Unit Binus University - Andi Nurul Sarah Bulqis (Bina Nusantara University, 2022)
Center For Business and Empowerment (CBSE) has committed to synergize and support the CDA Binus University. Coaching activities for Binus University-assisted MSMEs will develop from the previous activities which focused on providing competency and expertise training to Binus University-assisted MSME players by Binus University lecturers. As for improving the coaching program and to be more focused, CDA wants the MSME participants to be clusterized/categorized and then assessed or assessed their needs. The development model of computerization and needs assessment as well as the development of empowerment programs and curriculum for MSMEs assisted by BINUS hang includes 4 main stages and 1 reporting stage.